Wild edible plants for food security, dietary diversity, and nutraceuticals: a global overview of emerging research - Kumar, B. Mohan; Bhavya, Gurulingaiah; De Britto, Savitha; Jogaiah, Sudisha (Frontiers in Sustainable Food Systems, 2025)
Wild edible plants (WEPs) are integral to many local food systems. Historically, they improved the nutrition, dietary diversity and food security of indigenous communities. Integrating WEPs into local food systems represents a sustainable approach to reducing the carbon footprints of intensive farming and facilitating a shift toward more resilient food systems. Wild foods, rich in vitamins and minerals and a source of ethnomedicines, can enhance diets and promote health, longevity, and sustainability, especially among nutritionally disadvantaged groups. High biodiversity, local accessibility, cultural acquaintance, and low input needs are intrinsic features of wild foods. However, unsustainable harvesting and overexploitation, particularly in the tropical region, have led to depletion of these ecologically niche resources and their habitats, underscoring the need for conservation efforts to protect them. WEP research has gained momentum recently, with India and China emerging as forerunners in this domain. Considerable developments are also underway in the USA, Europe, and Africa. Such endeavors transect disparate fields, including food science and technology, plant sciences, sustainable agriculture, and phytochemistry. However, more efforts are essential in sustainable harvesting, plant domestication, valorization, and conservation.